'Necessity is the mother of invention': Specialist palliative care service innovation and practice change in response to COVID-19. Results from a multinational survey (CovPall). (May 2021) - Dunleavy, Lesley; Preston, Nancy; Bajwah, Sabrina; Bradshaw, Andy; Cripps, Rachel; Fraser, Lorna K; Maddocks, Matthew; Hocaoglu, Mevhibe; Murtagh, Fliss EM; Oluyase, Adejoke O; Sleeman, Katherine E; Higginson, Irene J; et al.
Background: Specialist palliative care services have a key role in a whole system response to COVID-19, a disease caused by the SARS-CoV-2 virus. There is a need to understand service response to share good practice and prepare for future care. Aim: To map and understand specialist palliative care services innovations and practice changes in response to COVID-19. Design: Online survey of specialist palliative care providers (CovPall), disseminated via key stakeholders. Data collected on service characteristics, innovations and changes in response to COVID-19. Statistical analysis included frequencies, proportions and means, and free-text comments were analysed using a qualitative framework approach. Setting/participants: Inpatient palliative care units, home nursing services, hospital and home palliative care teams from any country. Results: Four hundred and fifty-eight respondents: 277 UK, 85 Europe (except UK), 95 World (except UK and Europe), 1 missing country. 54.8% provided care across 2+ settings; 47.4% hospital palliative care teams, 57% in-patient palliative care units and 57% home palliative care teams. The crisis context meant services implemented rapid changes. Changes involved streamlining, extending and increasing outreach of services, using technology to facilitate communication, and implementing staff wellbeing innovations. Barriers included; fear and anxiety, duplication of effort, information overload and funding. Enablers included; collaborative teamwork, staff flexibility, a pre-existing IT infrastructure and strong leadership. Conclusions: Specialist palliative care services have been flexible, highly adaptive and have adopted low-cost solutions, also called 'frugal innovations', in response to COVID-19. In addition to financial support, greater collaboration is essential to minimise duplication of effort and optimise resource use. ISRCTN16561225 https://doi.org/10.1186/ISRCTN16561225